2021
DOI: 10.2478/rtuect-2021-0077
|View full text |Cite
|
Sign up to set email alerts
|

Emissions from 3D Printers as Occupational Environmental Pollutants

Abstract: While many people work remotely during the pandemic, three-dimensional (3D) printers are working to ensure the medical personnel and general public with the necessary specific materials. Ease of use, low cost, fast prototyping, and a wide range of materials are the advantages of 3D technology that can quickly adapt to specific needs in different application areas and result in increased popularity. The aim was to analyse the concentrations of particulate matter (PM) and volatile organic compounds (VOCs) emitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…And Dekati® ELPI® + measures during 3D printing show occupational exposure from 4x10 3 to 26x10 3 particles/cm 3 during 8-h shift. Furthermore, in all tested premises, the median diameter for particle number were detected: 0.014, 0.015, and 0.019 μm, but for mass concentrations: 4.394, 4.433, and 4.677 μm [46].…”
Section: Dust Measurementsmentioning
confidence: 83%
See 2 more Smart Citations
“…And Dekati® ELPI® + measures during 3D printing show occupational exposure from 4x10 3 to 26x10 3 particles/cm 3 during 8-h shift. Furthermore, in all tested premises, the median diameter for particle number were detected: 0.014, 0.015, and 0.019 μm, but for mass concentrations: 4.394, 4.433, and 4.677 μm [46].…”
Section: Dust Measurementsmentioning
confidence: 83%
“…VOCs and UFPs both have the potential adverse effect on human health through inhalation and skin contact, causing irritation, inflammation, lung disease, and various skin problems. It can also affect the central nervous system [36,38,46]. In addition, UFPs can pose health risks in a delayed manner even 1-5 days because of UFPs airborne exposure lag time.…”
Section: Toxicity and Health Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pavlovska i wsp. [10], którzy podczas 8-godzinnej zmiany ortopedów i projektantów opracowujących modele zmierzyli w strefie drukowania większej liczby drukarek 3D średnie stężenie cząstek ultradrobnych w zakresie od 4 × 10 3 do 26 × 10 3 cząstek/cm 3 .…”
Section: Substancje Chemiczne I Cząstki Stałe Emitowane Podczas Proce...unclassified
“…Nevertheless, using 3D printers has also raised concerns about the potential respiratory health hazards of releasing airborne particles during printing. Multiple studies revealed the increased concentration of different diameter PM and volatile organic compounds in the air samples taken during the printing [11] - [13].…”
Section: Introductionmentioning
confidence: 99%